2018
DOI: 10.1186/s12940-018-0360-7
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory health effects of exposure to low levels of airborne endotoxin – a systematic review

Abstract: BackgroundElevated endotoxin levels have been measured in ambient air around livestock farms, which is a cause of concern for neighbouring residents. There is clear evidence that occupational exposure to high concentrations of airborne endotoxin causes respiratory inflammation, respiratory symptoms and lung function decline. However, health effects of exposure to low levels of endotoxin are less well described. The aim of this systematic review is to summarize published associations between exposure to relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…Exposure to organic dust and high concentrations of endotoxin cause respiratory inflammation, respiratory symptoms, and declinations in lung function . There is variable evidence about the health effects associated with exposure to low endotoxin concentrations (less than 100 EU/m 3 ) but it has been reported that levels as low as 45 EU/m 3 may cause acute airflow obstruction, mucous membrane irritation, chest tightness, cough, shortness of breath, fever, and wheezing .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to organic dust and high concentrations of endotoxin cause respiratory inflammation, respiratory symptoms, and declinations in lung function . There is variable evidence about the health effects associated with exposure to low endotoxin concentrations (less than 100 EU/m 3 ) but it has been reported that levels as low as 45 EU/m 3 may cause acute airflow obstruction, mucous membrane irritation, chest tightness, cough, shortness of breath, fever, and wheezing .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiopulmonary markers including blood pressure, pulse, and heart rate variability are often considered (Cole-Hunter et al 2018). Lung function is evaluated using spirometry and often the Tiffeneau-Pinelli index (FEV 1 /FVC; forced expiratory volume in the first second/forced vital capacity) to compare exposed subjects with nonexposed controls (Farokhi, Heederik, and Smit 2018;Magzamen et al 2018). Blood samples from exposed subjects are commonly used to investigate inflammatory mechanisms or as exposure markers, either by measuring total and specific immunoglobins (IgE and IgG) or by determining blood levels of neutrophils, cytokines (tumor necrosis factor-α [TNF-α], interleukin-1β [IL-1β], or interleukin-6 [IL-6]).…”
Section: Summary Of Health Markersmentioning
confidence: 99%
“…Endotoxins produce a wide range of biological responses including blood vessel changes, inflammation, and allergic reactions. Airborne endotoxin exposures between 45 and 400 EU/m 3 have been associated with symptoms of cough, wheeze, shortness of breath, chest tightness, and mucous membrane irritation, and signs of acute airflow obstruction [Castellan et al 1987;Farokhi et al 2018;Milton et al 1996;Smid et al 1994]. Chronic health effects that have been associated with airborne endotoxin exposures include chronic bronchitis, bronchial hyperreactivity, chronic airways obstruction, hypersensitivity pneumonitis, and emphysema [Castellan 1995;Liebers et al 2008].…”
Section: Endotoxinmentioning
confidence: 99%